1977
DOI: 10.3382/ps.0560707
|View full text |Cite
|
Sign up to set email alerts
|

Influence of “CO2 Snow” Chilling on TBA Values in Mechanically Deboned Chicken Meat

Abstract: Mechanically deboned chicken meat (MDCM) precooled to 0° C. using carbon dioxide ("CO z snow") was obtained from a commercial processor along with MDCM which had not been precooled. Samples of both control (not precooled) and precooled meat were packaged in plastic pouches with and without vacuum, frozen and held in storage for six months at -18° C. 2-Thiobarbituric Acid (TBA) analyses were run on all samples at monthly intervals. The use of "C0 2 snow" resulted in rapid increases in TBA values after one month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The cryogenically frozen meat was expected to be superior in quality to the slowly frozen meat with respect to lipid oxidation. However, Uebersax et al (1977) reported that C0 2 chilling of comminuted meat resulted in higher TBA values than did chilling in air. The rapid freezing should result in less tissue damage, less breakdown of lipoprotein complexes, and less concentration of salts that could have a pro-oxidant effect.…”
Section: Resultsmentioning
confidence: 92%
“…The cryogenically frozen meat was expected to be superior in quality to the slowly frozen meat with respect to lipid oxidation. However, Uebersax et al (1977) reported that C0 2 chilling of comminuted meat resulted in higher TBA values than did chilling in air. The rapid freezing should result in less tissue damage, less breakdown of lipoprotein complexes, and less concentration of salts that could have a pro-oxidant effect.…”
Section: Resultsmentioning
confidence: 92%
“…Carbon dioxide snow has been used to chill mechanically deboned poultry meat rapidly for microbial control. This practice, however, has been found to increase TBA values in the products, indicating increased lipid oxidation (Uebersax et al, 1977;1978a;Mast et al, 1979).…”
Section: Functional Characteristicsmentioning
confidence: 95%